Public Higher Education Costs and College Enrollment - Taylor Delaney; Dave E. Marcotte (Institute of Labor Economics (IZA), 2022)
How have changes in the costs of enrolling full-time at public two- and four-year colleges affected student decisions about whether and where to enroll in college? Using local differences in the growth of tuition at community colleges and public four-year colleges we study the impact of public higher education costs on the post-secondary enrollment decisions of high school graduates over three decades. We model prospective students' decisions about whether to attend community college, a public four-year university in their state of residence, other colleges, or no college at all, as relative costs change. We identify enrollment impacts by instrumenting college costs using policy variation imposed by state appropriations and tuition caps. We estimate that in counties where local community college tuition doubled (about average for the study period), the likelihood of post-secondary enrollment fell by about 0.05, on a mean of about 0.80. In addition to reducing college enrollment overall, rising costs at community colleges diverted other students to four-year colleges. Rising relative costs of four-year public colleges similarly diverted some students toward community colleges but did not limit college attendance in the aggregate. We also find evidence of endogeneity in cost-setting at the institution level.
Keywords: I22; I23; 330; higher education; costs; enrollment